Feminist New Testament Studies - Wicker, K. author. aut Link
XIX, 268 p.
Keywords: This volume is an engaging and provocative introduction to Feminist Biblical Studies. The authors draw upon their own social, cultural and religious backgrounds and experiences in reading the New Testament as feminists in the context of globalization. They provide intentional interpretations of biblical texts that cast gender, race, class and power relationships as issues inherent in both the content and context of scripture and its interpretation. The essays call into question feminist social engagement that does not extend beyond academic halls, churches and Christians, suggesting directions for future research and teaching in Feminist Biblical Studies.